Floristic composition and dispersal syndromes at an urban remnant from the Atlantic forest in Brazilian Northeast - doi: 10.4025/actascibiolsci.v33i4.7142 (Acta Scientiarum. Biological Sciences, 2011)
Floristic composition and dispersal syndromes were determined along one year in an open ombrophilous forest fragment in the Municipal Park of Maceió, Alagoas State, Brazil. A total of 178 species belonging to 61 families were examined. Fabaceae was the most species-rich family, with 24 species. Among sampled species, 123 had their syndromes of diaspore dispersal determined, and most of them (69%) were zoochoric. Anemochoric and autochoric plants represent 11 and 20% from the total, respectively. The data about reproductive phases indicate coincident peaks of flowering and fruiting in August, at the end of the rainy season. The results are in accordance to those expected for ombrophilous forest with poorly defined seasonality.